2019
DOI: 10.7150/thno.37628
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of SMYD2 suppresses tumor progression by down-regulating microRNA-125b and attenuates multi-drug resistance in renal cell carcinoma

Abstract: SMYD2 is a histone methyltransferase that has been reported to be an important epigenetic regulator. This study aims to investigate SMYD2 as a prognostic indicator of clear cell renal cell carcinoma (ccRCC) and explore its role in tumorigenesis and multi-drug resistance.Methods: Tumor specimens, clinicopathologic information, and prognostic outcomes of 186 ccRCC patients from three hospitals in China were collected for SMYD2 immunohistochemistry staining, Kaplan-Meier analysis, and Cox proportional hazards-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…SMYD1 has been reported to be associated with several solid tumors, including breast cancer (40). Additionally, SMYD2 exhibited high expression in multiple types of tumors, including gastric cancer and colorectal cancer, and affected the migration and invasion of tumor cells (41,42). Combined with the results of the current study, we hypothesized that the development of inhibitors targeting SMYD family proteins has potential advantages for cancer targeted therapy.…”
Section: Discussionsupporting
confidence: 57%
“…SMYD1 has been reported to be associated with several solid tumors, including breast cancer (40). Additionally, SMYD2 exhibited high expression in multiple types of tumors, including gastric cancer and colorectal cancer, and affected the migration and invasion of tumor cells (41,42). Combined with the results of the current study, we hypothesized that the development of inhibitors targeting SMYD family proteins has potential advantages for cancer targeted therapy.…”
Section: Discussionsupporting
confidence: 57%
“…Molecular mechanisms that disrupt these pre-apoptotic signals are thought to be responsible for tumor resistance to chemotherapy ( 28 ). Thus, cisplatin has been the standard experimental drug to study the molecular mechanism of chemosensitivity in renal cell carcinoma ( 29 31 ). In accordance with these observations, the results of the present study demonstrated that high SIRT6 expression was associated with poor prognosis of patients with ccRCC, and SIRT6 knockdown decreased the proliferative, migratory and invasive abilities of ccRCC cells, and enhanced their sensitivity to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin pathway acts as one of the signaling pathways controlling EMT through directly or indirectly targeting several key transcription factors regulating E-cadherin expression and/or the fate of other epithelial molecules ( Valenta et al, 2012 ). SET and MYND domain-containing protein 2 (SMYD2), which acts as one of the SMYD-methyltransferase protein family and specifically methylates H3K4 through its SET domain ( Abu-Farha et al, 2008 ), is deemed to regulate the expression of miR-125b ( Yan et al, 2019 ). miR-125b bind directly to the 3'-UTR of DKK3, a key regulatory factor in the Wnt/β-catenin pathway which acts as a tumor suppressor in RCC ( Lu et al, 2017 ).…”
Section: An Overview Of Epigenetic Modificationmentioning
confidence: 99%
“…miR-125b bind directly to the 3'-UTR of DKK3, a key regulatory factor in the Wnt/β-catenin pathway which acts as a tumor suppressor in RCC ( Lu et al, 2017 ). Thus, the activation of SMYD2/miRNA-EMT pathway weakens the effect sunitinib treatment and accelerates the tumor growth ( Yan et al, 2019 ).…”
Section: An Overview Of Epigenetic Modificationmentioning
confidence: 99%